2000
DOI: 10.1136/jech.54.11.827
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in the Danish general population. Influence of sociodemographic factors and disease

Abstract: Objective-To measure the levels of fatigue in the general population, and to examine how disease and sociodemographic factors influence fatigue. Results-Fatigue scores were skewed towards absence of fatigue. The General Fatigue and Physical Fatigue scales showed the highest fatigue levels while the Reduced Motivation scale showed lowest levels. Gender diVerences in fatigue scores were small, but the variability among women was higher-that is, more women had high scores. A multiple linear regression analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
158
8
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(201 citation statements)
references
References 62 publications
29
158
8
5
Order By: Relevance
“…An explanation why the patients in the last study experienced more reduced ability to accomplish activities is their signifi cantly poorer functional status (higher NYHA class) (p = ≤0.001). The patients in Study I and II reported signifi cantly higher fatigue scores in all MFI-20 fatigue dimensions as compared with a general Nordic population (p = ≤ 0.001) (Watt et al, 2000). This fi nding verifi es that patients with CHF experience fatigue to greater extent compared with persons of the same age.…”
Section: Summarize Of the Main Fi Ndingssupporting
confidence: 55%
“…An explanation why the patients in the last study experienced more reduced ability to accomplish activities is their signifi cantly poorer functional status (higher NYHA class) (p = ≤0.001). The patients in Study I and II reported signifi cantly higher fatigue scores in all MFI-20 fatigue dimensions as compared with a general Nordic population (p = ≤ 0.001) (Watt et al, 2000). This fi nding verifi es that patients with CHF experience fatigue to greater extent compared with persons of the same age.…”
Section: Summarize Of the Main Fi Ndingssupporting
confidence: 55%
“…Some authors found no correlation (18,19); one study (20) found that the prevalence of both chronic and non-chronic fatigue decreases with age; others found a positive correlation (1,12,21,22). The results from the Danish population study among a random sample of 16-77-year-olds (17) may explain the ambiguity in this research. Fatigue decreased with age in the healthy part of the population, but increased with age among those with a chronic disease.…”
Section: Introductionmentioning
confidence: 70%
“…Several cross-sectional studies have shown associations between depression or depressive symptoms and fatigue (17,135) and development of fatigue (15,136,137). However, when adjusting the associations between fatigue and diverse outcomes by depressive symptoms, the results did not seriously change (33,58,62,64).…”
Section: Depressionmentioning
confidence: 77%
See 1 more Smart Citation
“…19 MFI-20 data were compared against an age-stratified general population sample of 1,608 randomly selected Danish men and women aged 20 to 79 years in a study of fatigue in the Danish general population. 24 Finally, HAD general population data were obtained from a study comparing anxiety and depression in patients with breast cancer against a sample of 872 women aged 31 to 75 years who were randomly selected from the Danish general population. 25 …”
Section: General Population Datamentioning
confidence: 99%